PEMBENTUKAN DAN OPTIMALISASI PERAN KADER MASYARAKAT DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI DESA PONGOK BANGKA SELATAN - Azmy, Restu Amalia; Elni; Mardiyah, Adiyati; Maktum, Ummi; Pratama, Deni (P3M Universitas Aisyiyah Surakarta, 2025)
The problem that occurs in the Pongok Community is the lack of awareness and knowledge of the Pongok village community regarding the disposal and management of household waste. The community disposes of rubbish by throwing it into the sea and burning it. Village cadres have not yet been formed for waste management in Pongok village. There are health impacts from the effects of burning rubbish such as respiratory diseases and problems with the fetus during pregnancy. The target of this activity is Pongok community cadres, and the outcome is that the cadres are expected to be able to make household waste management more useful. The method used in this service is to increase cadres' knowledge and demonstrate the management of household waste that can be recycled, so that it can change people's behavior. The method used in this service is a health education approach, training and cadre formation. The results of the evaluation and monitoring of the activities that have been carried out show positive results, namely increasing cadres' knowledge about household waste management and cadres being able to turn household waste into liquid organic fertilizer (POC)